Upregulation of the transient receptor potential ankyrin 1 ion channel in the inflamed human and mouse colon and its protective roles. - József Kun (Public Library of Science (PLoS), 2014)
Transient Receptor Potential Ankyrin 1 (TRPA1) channels are localized on sensory nerves and several non-neural cells, but data on their functional significance are contradictory. We analysed the presence and alterations of TRPA1 in comparison with TRP Vanilloid 1 (TRPV1) at mRNA and protein levels in human and mouse intact and inflamed colons. The role of TRPA1 in a colitis model was investigated using gene-deficient mice. TRPA1 and TRPV1 expressions were investigated in human colon biopsies of healthy subjects and patients with inflammatory bowel diseases (IBD: ulcerative colitis, Crohn's disease) with quantitative PCR and immunohistochemistry. Mouse colitis was induced by oral 2% dextran-sulphate (DSS) for 10 days. For investigating the functions of TRPA1, Disease Activity Index (weight loss, stool consistency, blood content) was determined in C57BL/6-based Trpa1-deficient (knockout: KO) and wildtype (WT) mice. Sensory neuropeptides, their receptors, and inflammatory cytokines/chemokines were determined with qPCR or Luminex. In human and mouse colons TRPA1 and TRPV1 are located on epithelial cells, macrophages, enteric ganglia. Significant upregulation of TRPA1 mRNA was detected in inflamed samples. In Trpa1 KO mice, Disease Activity Index was significantly higher compared to WTs. It could be explained by the greater levels of substance P, neurokinins A and B, neurokinin 1 receptor, pituitary adenylate-cyclase activating polypeptide, vasoactive intestinal polypeptide, and also interleukin-1beta, macrophage chemoattractant protein-1, monokine induced by gamma interferon-1, tumor necrosis factor-alpha and B-lymphocyte chemoattractant in the distal colon. TRPA1 is upregulated in colitis and its activation exerts protective roles by decreasing the expressions of several proinflammatory neuropeptides, cytokines and chemokines.